ANALISIS PEMANFAATAN EKOWISATA HUTAN MANGROVE SEBAGAI SUMBER BELAJAR PADA SISWA SEKOLAH DASAR - Thasya Angraini Imamah; Anang Kurniawan; Naylul Kamiliyah; Rizka Rohmatul Asyura; Yetti Hidayatillah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research discusses the development of mangrove forest ecotourism as a sustainable learning medium that contributes to the welfare of local communities and environmental conservation. Mangrove forest ecotourism not only provides ecological benefits, such as coastal protection and carbon sequestration, but also supports environmental education through hands-on experiences that can increase students' awareness of the importance of nature conservation. This research identifies the potential of mangrove forests as a learning resource that fits into the education curriculum, as well as exploring its benefits in improving student competencies. In addition, this research revealed challenges faced in the development of ecotourism, such as limited infrastructure and promotion, as well as the need for supportive regulations. The positive impacts of mangrove forest ecotourism on the community include changes in mindset and the creation of new economic opportunities, although there are potential negative impacts such as social conflict and criminality.